The Prolongation of Pulse Transit Time After a Stellate Ganglion Block: An Objective Indicator of a Successful Block - Young Uk Kim; Yuseon Cheong; Yu Gyeong Kong; Jonghyuk Lee; Sehun Kim; Hong Gyu Choi; Jeong Hun Suh (Pain Research and Management)
The relationship between the change of pulse transit time and the presence of clinical signs after stallate ganglion block (SGB) was investigated in patients with disorders mediated by the sympathetic nervous system. SGB is used for the treatment and diagnosis of these disorders; however, a successful objective marker does not exist. Therefore, identifying increased blood flow following SGB and determining whether pulse transit time could be used to verify the success of SBG would be a helpful resource.